PENGARUH ATRIBUT PRODUK WISATA DAN WORD OF MOUTH TERHADAP KEPUTUSAN BERKUNJUNG PADA OBJEK WISATA TAMAN MARGASATWA SEMARANG - Widya Muna Mayasari; Agung Budiatmo (Universitas Diponegoro, 2017)
Tourism is one of industry that is growing rapidly. As a result, traveled has become a part of the human necessities . This phenomenon causes the number of tourist arrivals in the city of Semarang is increasing. Has contributed to an increase experienced by Taman Margasatwa Semarang, a tourist attraction concept Conservation, Recreational, Education, and Research in the area of West Semarang. This study aims to determine the influence of Tourism Product Attribute and Word of Mouth to the Tourism Decision to visit Taman Margasatwa Semarang. This type of research is explanatory research where data collection techniques used is by means of questionnaire, the selected sample of 100 people with purposive sampling. Respondents are visitor attractions Taman Margasatwa Semarang who had never been at the Taman Margasatwa Semarang and find out information Taman Margasatwa Semarang from others The results showed that the attributes of travel products and significant influence on the decision to visit by contributing 32.7% and the rest is explained by other factors. Word of mouth and significant influence on the decision to visit by donating 35% and the rest is explained by other factors. Meanwhile, simultaneous attributes of the tourism product and word of mouth influence and significant impact on the decision to visit. Means the better attributes of the tourism product and word of mouth, the higher the decision been Attractions: Wildlife Areas Semarang. Besides word of mouth has the most dominant influence with regression coefficient of 0.472. The results obtained by analyzing primary data using validity, reliability test, correlation coefficient, determination coefficient, simple linear regression, multiple linear regression, and a significance test (t test and F) with SPSS 22.0 Based on the results of the study, the researchers suggested that UPTD Taman Margasatwa Semarang re-analyze the pricing policy in order to get the quality and benefit traveled better, increasing promotion through a wide range of marketing communications, and gives a good impression on visitors.